Pengaruh Content Marketing dan Brand Awareness Terhadap Costumer Engagement Ditinjau dari Perspektif Ekonomi Islam - Farma, Junia; Natasyrah, Zafira; Ilyas, Fithriady (Program Studi Perbankan Syariah FEBI UIN Ar-Raniry, 2025)
The development of marketing communication has become easier thanks to content marketing and brand awareness strategies, which are widely used by companies. This study aims to analyze the effect of content marketing and brand awareness on customer loyalty of Kopi Memangan in Banda Aceh City from an Islamic economic perspective. The population in this study included all consumers of Kopi Memangan in Banda Aceh City. This research uses quantitative approach. The sample used amounted to 100 respondents with accidental sampling technique. The data analysis technique used is multiple linear regression and hypothesis testing. The results showed that: (1) content marketing and brand awareness simultaneously have a positive and significant effect on customer commitment of memorable coffee in Banda Aceh City; (2) content marketing partially has a positive and significant effect on customer commitment of memorable coffee in Banda Aceh City; and (3) brand awareness also partially has a positive and significant effect on customer commitment of memorable coffee in Banda Aceh City.